Strategies to Minimize Human Error: Applications in the Pharmaceutical Industry - Souza, Leandro Luiz Soares de; Terra, Leonardo Augusto Amaral (Archives of Business Research, 2025)
Given the magnitude of the pharmaceutical industry, human errors in production processes have a significant impact on operations and manufacturing activities, representing one of the major challenges faced in this business sector. This research aims to identify the best practices within industry to minimize human errors. Through exploratory research with specialists working in diverse industries, including small, medium, and large-scale national and multinational companies, using a semi-structured questionnaire analyzed via a mental map, We have identified the following good practices for error reduction: Training; Error Mapping; Documentation; Process Automation; Competency Evaluation; and Open Communication Culture. These six best practices were ranked and analyzed in detail and contrast with previous research that points to exhaustion as the main cause of human error in the pharmaceutical industry.